Bodenkundliche Differenzierungen in Flurwüstungen - Niemeier, Georg (ERDKUNDE, 1967)
The study of desertion has been stimulated in Germany by the study and mapping of ridge-and-furrow (Wölbacker), especially under forest, and has obtained new types of evidence for the genesis of the cultural landscape. But new problems are thereby created. The dating of field desertions can be uncertain even when they lie in the vicinity of well localised and dated village desertions. Some ridge-and-furrow complexes are so extensive that they are too large for the village desertions they are matched with. It has been calculated that every deserted farmstead could have 50 or more hectares of arable land and this goes far over the standard found in the evidence. Using examples from SE Lower Saxony, it is shown that pedological mapping of ridge-and-furrow areas can contribute towards answering such questions. The example of Martinsbüttel is taken to show that the Papenholz field desertion ascribed to this village was not a field core (Flurkern) but a peripheral field section, partly indeed for surviving villages (mostly moist soils with former shifting land use as outfield). In contrast, the example of Hohnstedt shows a Plaggen-soil complex of adequate size and located 'properly' to the village desertion as the field core and one-time permanent arable land, with large surrounding areas of moist soils. Apart from that, the discrepancy between soil type boundaries and parcel form allows one to presume that the ridge-and-furrow complexes were transformed after the desertion of the village.